Antibacterial activity of a Tribolium castaneum defensin in an in vitro infection model of Streptococcus pneumoniae. Issue 1 (1st January 2019) - Lindhauer, Nora S.; Bertrams, Wilhelm; Pöppel, Anne; Herkt, Christina E.; Wesener, Andre; Hoffmann, Kerstin; Greene, Brandon; Van Der Linden, Mark; Vilcinskas, Andreas; Seidel, Kerstin; Schmeck, Bernd
ABSTRACT: Streptococcus pneumoniae ( S. pneumoniae ) is the most common bacterial cause of community-acquired pneumonia. Increasing rates of antibiotic-resistant S. pneumoniae strains impair therapy and necessitate alternative treatment options. In this study, we analysed insect-derived antimicrobial peptides (AMPs) for antibacterial effects on S. pneumoniae in a human in vitro infection model. AMP effects on bacterial growth were examined by colony forming unit (CFU)-assays, and growth curve measurements. Furthermore, cytotoxicity to primary human macrophages was detected by measuring lactate-dehydrogenase release to the supernatant. One AMP (Defensin 1) was tested in a model of primary human monocyte-derived macrophages infected with S. pneumoniae strain D39 and a multi-resistant clinical isolate. Inflammatory reactions were characterised by qPCR and multiplex-ELISA. In total, the antibacterial effects of 23 AMPs were characterized. Only Tribolium castaneum Defensin 1 showed significant antibacterial effects against S. pneumoniae strain D39 and a multi-resistant clinical isolate. During in vitro infection of primary human macrophages with S. pneumoniae D39, Defensin 1 displayed strong antibacterial effects, and consequently reduced bacteria-induced cytokine expression and release. In summary, Tribolium castaneum Defensin 1 showed profound antibacterial effectivity against Streptococcus pneumoniae D39 and a multi-resistant clinical isolate without unwanted cytotoxic or inflammatory side effects on human blood-derived macrophages.